Water Resource Management – Ghana - Siakwa, Augustine Narkorli Kwesi (Journal of Central European Green Innovation, 2023)
Having a tropical climate, Ghana experience high rainfall per year making water resources abundant in the country. The major water resources in the country include; lakes, rivers, streams, ponds and groundwater. Unfortunately, the management of these water resources by ensuring there is sufficient water of adequate quality for drinking and other benefits has been a challenge to government institutions responsible for the planning and execution of policies to manage and sustain these resources. The three major management problem are pollution, flood, and drought. The Government of Ghana in 2022 uses key tracker and indicator as an innovative way of monitoring the progress made in the country’s effort to address menace of illegal mining that pollute water resources in Ghana (ENVIRONMENTAL PROTECTION AGENCY, 2023). Dam safety Regulation LI 2236 of 2016 was established as an innovative way safeguarding dams to prevent flooding (WATER RESOURCES COMMISSION, 2021). Small and medium enterprises (SMEs) and consultants use treated sludges and waste water for nursing vegetable seedlings, flash flood forecasting app for detecting early flood warning, using technology to recycle carwash water for re-use. The Environmental Protection Agency (EPA) together with United Nations Framework Convention on Climate Change (UNFCC) through the Capacity Building Initiative for transparency (CBIT) project was aimed at strengthening the effectiveness of Ghana climate ambitious reporting programme for climate action and support (ENVIRONMENTAL PROTECTION AGENCY, 2023). Cooperation in International Waters in Africa (CIWA) a project of World bank, The Sahel groundwater Initiative by CIWA, Transboundary water management in Africa by European union and other initiatives seeks to assist Africa including Ghana with innovation ways in realizing the United Nation Sustainable Development Goals (SDG6) which calls for ensuring the availability and sustainable management of water and sanitation for all by 2030. The government and the institutions responsible for safe guarding the water resources must invest in innovative methods in managing this great resource.
Keywords: water resource management; Ghana; innovation; pollution; international cooperation